Babu and Magon uterine closure technique during cesarean section: A randomized double‐blind trial. Issue 9 (15th June 2021) - Tahermanesh, Kobra; Mirgalobayat, Shahla; Aziz‐Ahari, Alireza; Maleki, Maryam; Hashemi, Neda; Samimi, Mansooreh; Fazel Anvari‐Yazdi, Abbas; Shahriyaripour, Roya; Pecks, Ulrich; Allahqoli, Leila; Alkatout, Ibrahim
Abstract: Aim: We compared the effectiveness of the Babu and Magon uterine closure technique and unlocked double‐layer uterine closure on the integrity and thickness of the uterine scar. Methods: A randomized double‐blind trial was performed at Hazrat‐e Rasoul ‐e‐Akram Hospital, Tehran, Iran, from March 2018 to December 2019, in 72 pregnant women who were candidates for cesarean section for the first time. Women were randomly assigned to the Babu and Magon uterine closure technique (intervention group, n  = 34) or double‐layer closure of the uterine incision (control group, n  = 38). The primary outcome of the study was the frequency of myometrial defects at the site of the scar (niche), and a large niche. Secondary outcomes, including the time taken for uterine closure and postpartum hemorrhage (early and late), were compared between groups. Results: Adjacent myometrium thickness (AMT) between the two groups was not statistically significant. A niche was reported in 23.5% (8/34) and 50% (19/38) of women in the intervention and controls, respectively ( p  = 0.02). A large niche was reported in 2.9% (1/34) and 23.7% (9/38) of women in the intervention and controls, respectively ( p  < 0.01). The duration of uterine closure was not statistically significant between the two groups. Hemoglobin levels did not differ significantly between groups during the first 24 h post‐surgery. Conclusion: The results of the study showed that the technique of uterine closure is one of the main potential determinants of myometrial healing. The Babu and Magon uterine closure technique seems to lead to tissue alignment during suturing and consequently cause better myometrial healing, although this issue calls for well‐founded longer studies of appropriate design.